0

# What is 24a plus b2 plus 3a plus 2b2?

Updated: 9/16/2023

Wiki User

14y ago

24a + b2 + 3a + 2b2

= 27a + 3b2

Wiki User

14y ago

Earn +20 pts
Q: What is 24a plus b2 plus 3a plus 2b2?
Submit
Still have questions?
Related questions

### What is b2 plus 3b-5b plus 2b2?

We can combine the like terms. So the b2 can be combined with the 2b2 to give 3b2. Likewise the 3b plus the -5b gives -2b.Therefore, b2 + 3b - 5b + 2b2 = 3b2 - 2b.

### B to the second plus b to the second?

b2 + b2 = 2b2 (when terms are alike, just add them up)

### Find the illegal values of b in the fraction 2b2 plus 3b-10 over b2-2b-8?

2b2 + 8 para b = -3

### What is b squared plus ab minus two minus two b squared plus two ab?

b2 + ab - 2 - 2b2 + 2ab = -b2 + ab - 2 which cannot be simplified further.

a(b+3)+b(b+3)

### Ab plus 3a plus b squared plus 3b?

This expression can be factored. ab + 3a + b2 + 3b = a(b + 3) + b(b + 3) = (a + b)(b + 3)

(3a + b)(3a - b)

### How can you factor the statement 9a4 - b2?

Assuming the exponential form, 9a4 - b2 has the factors (3a + b)(3a - b).

### Factor b3 - 5b2 plus 12?

b3 - 5b2 + 12 = (b - 2)(b2 - 3b - 6)Check:(b - 2)(b2 - 3b - 6)= b(b2 - 3b - 6) - 2(b2 - 3b - 6)= b3 - 3b2 - 6b - 2b2 + 6b + 12= b3 - 5b2 + 12

### How do you factor 9A2-B2?

There is a formula for the "difference of squares." In this case, the answer is (3A + B)(3A - B)

### The eccentricity of the ellipse if minor axis is equal to the distance between the foci is Answer is 1 radical 2 how?

The standard equation for an ellipse centered at the origin is [x2/a2] + [y2/b2] = 1 We also have the relationship, b2 = a2 - c2 where c is the distance of the foci from the centre and a &amp; b are the half lengths of the major and minor axes respectively. When the length of the minor axis equals the distance between the two foci then 2b = 2c : b = c. Thus, a2 =b2 + c2 = 2b2 One of the formulae for the eccentricity of an ellipse is, e = &radic;[(a2 - b2)/a2] Thus, e = &radic;[(2b2 - b2) / 2b2] = &radic;&frac12; = 1/&radic;2.

### Reduce -8 plus b2 by 5 plus b2?

(-8 + b2) - (5 + b2) = -8 + b2 - 5 - b2 = -13